Conventional echocardiographic parameters or three-dimensional echocardiography to evaluate right ventricular function in percutaneous edge-to-edge mitral valve repair (PMVR). (September 2019) - Sauter, Reinhard J.; Patzelt, Johannes; Mezger, Matthias; Nording, Henry; Reil, Jan-Christian; Saad, Mohammed; Seizer, Peter; Schreieck, Juergen; Rosenberger, Peter; Langer, Harald F.; Magunia, Harry
Abstract: Introduction: In this study, we evaluated right ventricular (RV) function before and after percutaneous mitral valve repair (PMVR) using conventional echocardiographic parameters and novel 3DE data sets acquired prior to and directly after the procedure. Patients and methods: Observational study on 45 patients undergoing PMVR at an university hospital. Results: In the overall collective, the 3D RV-EF before and after PMVR showed no significant change (p = 0.16). While there was a significant increase of the fractional area change (FAC, from 23 [19–29] % to 28 [24–33] %, p = 0.001), no significant change of the tricuspid annular plane systolic excursion (TAPSE, from 17 ± 6 mm to 18 ± 5 mm (standard deviation), p = 0.33) was observed. Regarding patients with a reduced RV-EF (< 35%), a significant RV-EF improvement was observed (from 27 [23–34] % to 32.5 [30–39] % (p = 0.001). 71.4% of patients had an improved clinical outcome (improvement in 6-minute walk test and/or improvement in NYHA class of more than one grade), whereas clinical outcome did not improve in 28.6% of patients. Using univariate logistic regression analysis, the post-PMVR RV-EF (OR 1.15: 95% CI 1.02–1.29; p = 0.02) and the change in RV-EF (OR 1.13: 95% CI 1.02–1.25; p = 0.02) were significant predictors for improved clinical outcome at 6 months follow up. Conclusion: Thus, RV function may be an important non-invasive parameter to add to the predictive parameters indicating a potential clinical benefit from treatment of severe mitral regurgitation using PMVR.